The cause and frequency of PES Planus (Flat Foot) problems among young adults - R, Azhagiri; Malar, Anitha; J, Hemapriya; G, Sumathi (Asian Journal of Medical Sciences, 2021)
Background: Pes planus, also known as flat foot, is one of the most commonly seen foot deformity. It is characterized by a very low or an absent arch, which is the main supportive structure of the foot. Pes planus deformity is associated with impaired foot movements and increased frequency of pain and discomfort. Aims and Objectives: The present study was carried out to estimate the prevalence of pes planus among young healthy individuals in South Indian population. Materials and Methods: This cross-sectional study was carried out among 500 individuals (168 males and 332 females) between the ages of 18 and 25 years. The feet of all subjects were visually inspected and footprint screening test was carried out. Results: The prevalence of pes planus among the study subjects was 29%. The highest prevalence and pattern of age wise distribution of pes planus was observed in 20 years (24%), followed by 18years (16%), 19& 21years (14%), 23years (13%), and 22,24&25 years (10%,6%,3% respectively). Conclusion: Regular screening and monitoring of this foot deformity would create awareness about foot problems and can guide care givers to provide suitable footwear for persons with pes planus. It is advisable to conduct early screening so as to reduce the flatfoot progression into the adulthood and would assist better in their physical activities.